Editorial: Stowaways of a Stowaway: Parasites of Invasive Rodents - Ribas, Alexis; Henttonen, Heikki; Morand, Serge (Frontiers Media SA, 2022)
Human-induced ecosystem modifications include the introduction of alien species, among which rodents are particularly widespread. The expansion and adaptations of invasive rodents, which can come from distant regions, even different continents, have a wide spectrum of ecological consequences, including the spread of parasites and pathogens. As the title of this Research Topic reflects, the parasites travel to these newly colonized areas as stowaways on a stowaway.
Keywords: rodents; zoonosis; invasion; parasite; Rattus; Mastomys; Mus